The role of gender in a large international OCD sample: A Report from the International College of Obsessive-Compulsive Spectrum Disorders (ICOCS) Network - Beatrice Benatti; Nicolaja Girone; Laura Celebre; Matteo Vismara; Eric Hollander; Naomi A. Fineberg; Dan J. Stein; Humberto Nicolini; Nuria Lanzagorta; Donatella Marazziti; Stefano Pallanti; Michael van Ameringen; et al. (Comprehensive Psychiatry, 2022)
Introduction: Obsessive-compulsive disorder (OCD) is characterized by a range of phenotypic expressions. Gender may be a relevant factor in mediating the disorder's heterogeneity. The aim of the present report was to explore a large multisite clinical sample of OCD patients, hypothesizing existing demographic, geographical and clinical differences between male and female patients with OCD. Methods: Socio-demographic and clinical variables of 491 adult OCD outpatients recruited in the International College of Obsessive-Compulsive Spectrum Disorders (ICOCS) network were investigated with a retrospective analysis on a previously gathered set of data from eleven countries worldwide. Patients were assessed through structured clinical interviews, the Yale- Brown Obsessive-Compulsive Scale (Y-BOCS), the Montgomery-Asberg Depression Rating Scale (MADRS) and the Self-rating Depression Scale (SDS). Results: Among females, adult onset (>18 years old) was significantly over-represented (67% vs. 33%, p < 0.005), and females showed a significantly older age at illness onset compared with males (20.85 ± 10.76 vs. 17.71 ± 8.96 years, p < 0.005). Females also had a significantly lower education level than males (13.09 ± 4.02 vs. 13.98 ± 3.85 years; p < 0.05), a significantly higher rate of being married (50.8% vs. 33.5%; p < 0.001) and a higher rate of living with a partner (47.5% vs. 37.6%; p < 0.001) than males. Nonetheless, no significant gender differences emerged in terms of the severity of OCD symptoms nor in the severity of comorbid depressive symptoms. No predictive effect of gender was found for Y-BOCS, MADRS and SDS severity. Discussion/Conclusions.: Our findings showed significant differences between genders in OCD. A sexually dimorphic pattern of genetic susceptibility may have a crucial role to OCD clinical heterogeneity, potentially requiring different specific therapeutic strategies. Further research is warranted to validate gender as an important determinant of the heterogeneity in OCD.